Numerical investigation on solitary waves traveling over rigid vegetation by a 3D-MPS method. (March 2023) - Wang, Lizhu; Xu, Min; Zhang, Changle; Dai, Weiqi
Abstract: In this study, a three-dimensional wave-vegetation numerical model based on the moving particle semi-implicit (MPS) method is established to investigate the interaction between solitary waves and rigid vegetation. Different from traditional wave-vegetation models, the effect of vegetation in the present numerical model is considered in terms of the stress between fluid and solid particles. Several improvements are put forward to increase the simulation accuracy, including a higher-order pressure gradient discrete model, a multi-term source involving a background mesh scheme, and multi-condition free surface detection. Based on the improved 3D-MPS method, the propagation of solitary waves on a flat bed with and without vegetation is simulated. The results show improvement in resolving the issue of numerical energy dissipation. Because of the intrinsic advantage of the particle method, the attenuation and deformation of a wave on a vegetation area can be realistically reproduced, as can detailed velocity and curl fields. In addition, a parametric study of the effects of wave height, plant relative height, and stem density on the wave attenuation rate is conducted. The result indicates that the relationship between wave attenuation rate and plant height is nonlinear.